Workshop on Computational Methods in CyberSafety, Online Harassment and Misinformation, co-located with the Web Conference: Distinguished Paper - Sirivianos, Michael (My University, 2026)
2019: Workshop on Computational Methods in CyberSafety, Online Harassment and Misinformation, co-located with the Web Conference - Distinguished Paper “Disinformation Warfare: Understanding State-Sponsored Trolls on Twitter and Their Influence on the Web”
Keywords: Sciences